Inculcation Method of Character Education Based on Personality Types Classification in Realizing Indonesia Golden Generation - M.J. Dewiyani Sunarto; Tri Sagirani (International Journal of Evaluation and Research in Education (IJERE), 2014)
"The rise of Indonesia Golden Generation" is the theme of National Education Day in 2012, In an effort to create a golden generation, education must be interpreted as a complex problem, in particular the cultivation of character education that was originally using indoctrination method. Given the shifting of the changing times,indoctrination methods are imprecise because young people today would not accept the doctrine of no logic that can be digested. Regarding the condition, this research has to find a method that more focus on thinking process which can be accepted by learners. The method used is the inculcation method. The inculcation method will be approached through different personality types that are classified based on the type of personality by David Keirsey. Using exploratory qualitative approach for curricular activities and natural activitiesforextra-curricular activities, the research obtained the character education inculcation method that more personal, so this will be move striking for self learner, as it is based on the profile of each individual's cognitive (thinking) process on the personality type. The development of this research is the creation of a character education learning model with inculcation method based on classification of personality type.DOI: http://dx.doi.org/10.11591/ijere.v3i2.4199